An enhanced dq-based vector control system for modular multilevel converters feeding variable speed drives - Espinoza, Mauricio; Cardenas, Roberto; Diaz, Matias; Clare, Jon C. (Institute of Electrical and Electronics Engineers, 2017)
Modular multilevel converters (M2C) are considered an attractive solution for high power drive applications. However, energy balancing within the converter is complex to achieve, particularly when the machine is operating at low rotational speeds. In this paper, a new control system, based on cascaded control loops and a vector-power-voltage (vPV) model of the M2C, is proposed. The control system is implemented in a dq-synchronous frame rotating at ωe rad/s with the external loop regulating the capacitor voltages using proportional-integral (PI) controllers. The internal loop controls the converter currents using PI and resonant controllers. In addition, the control systems required to operate the machine at other points, i.e., at medium and high rotational speeds, are also discussed in this paper. Experimental results obtained with an M2C-based drive laboratory prototype with 18 power cells are presented in this paper.